Synthesis and properties of open fullerenes encapsulating ammonia and methane - Bloodworth, Sally; Gräsvik, John; Alom, Shamim; Kouril,, Karel; Elliott, Stuart J.; Wells, Neil J.; Horsewill, Anthony J.; Mamone, Salvatore; Jimenez-Ruiz, Monica; Rols, Stéphane; Nagel, Urmas; Room, Toomas; et al. (Wiley, 2018)
We describe the synthesis and characterisation of open fullerene (1) and its reduced form (2) in which CH₄ and NH₃ are encapsulated, respectively. The ¹H NMR resonance of endohedral NH₃ is broadened by scalar coupling to the quadrupolar ¹⁴N nucleus, which relaxes rapidly. This broadening is absent for small satellite peaks, which are attributed to natural abundance ¹⁵N. The influence of the scalar relaxation mechanism on the linewidth of the ¹H ammonia resonance is probed by variable temperature NMR. A rotational correlation time of τc= 1.5 ps. is determined for endohedral NH₃, and of τc=57±5 ps. for the open fullerene, indicating free rotation of the encapsulated molecule. IR spectroscopy of NH3@2 at 5 K identifies three vibrations of NH₃ (ν₁, ν₃ and ν₄) redshifted in comparison with free NH₃, and temperature dependence of the IR peak intensity indicates the presence of a large number of excited translational/ rotational states. Variable temperature ¹H NMR spectra indicate that endohedral CH4 is also able to rotate freely at 223 K, on the NMR timescale. Inelastic neutron scattering (INS) spectra of CH₄@1 show both rotational and translational modes of CH₄. Energy of the first excited rotational state (J=1) of CH₄@1 is significantly lower than that of free CH₄.